2014
DOI: 10.4238/2014.december.4.30
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of inflorescence in common bean

Abstract: ABSTRACT. The number of pods per common bean plant is a primary component of grain yield, which depends on the number of flowers produced and on the flower set. Thus, a larger number of flowers per plant would increase yield. Lines with inflorescences that had a large number of flowers compared to common bean plants now under cultivation were identified. We analyzed the genetic control of this trait and its association with grain yield. The cultivar BRSMG Talismã was crossed with 2 lines, L.59583 and L.59692, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Several studies have reported the presence of genes with an additive effect, similar to those found in the present study (Takeda et al, 1991;Vizgarra et al, 1992;Silva et al, 2004;Moreto et al, 2007). However, there are reports that occurrence of dominance was also important in W (Chung and Stevenson, 1973;Foolad and Bassiri, 1983;Guilherme et al, 2014).…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…Several studies have reported the presence of genes with an additive effect, similar to those found in the present study (Takeda et al, 1991;Vizgarra et al, 1992;Silva et al, 2004;Moreto et al, 2007). However, there are reports that occurrence of dominance was also important in W (Chung and Stevenson, 1973;Foolad and Bassiri, 1983;Guilherme et al, 2014).…”
Section: Discussionsupporting
confidence: 39%
“…The number of pods per plant (X) in common bean is one of the most important components for initial yield, as already mentioned (Costa and Zimmermann, 1988;Zilio et al, 2011;Guilherme et al, 2014). The number of pods depends on the number of flowers produced (N) and the percentage of pod set (V).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation